Survival and cost comparison of kyphoplasty and percutaneous vertebroplasty using German claims data - Lange, Ansgar; Kasperk, Christian; Alvares, Luisa; Sauermann, Sven; Braun, Sebastian (Spine, 2014)
Study Design. - Observational study. -Objective. - Examine the overall survival and treatment costs from a third-party-payer perspective for patients with osteoporotic vertebral compression fractures (OVCFs) treated by vertebral augmentation or conservative treatment in Germany. - Summary of Background Data. -OVCFs are associated with increased morbidity, mortality and thus reduced quality of life. Vertebral augmentation has been shown to be effective in these fractures. The association between treatment and survivorship as well as cost per life year gained for balloon kyphoplasty (BKP) and percutaneous vertebroplasty (PVP) was analyzed in the Medicare population. Replication of these analyses is warranted for confidence in findings. - Methods. - Claims data from a major health insurance fund were used. Mortality risk differences between operated (BKP, PVP) and nonoperated cohorts were assessed by Cox regression. Operated patient groups were established by propensity score matching adjusting for covariates. For the matched operated patients with OVCF, (2006-2010) survival was estimated by Kaplan-Meier method. -Results. -A total of 598 newly diagnosed patients with OVCF were operated of 3607 patients with OVCF. The operated cohort was 43% less likely to die than the nonoperated one in the 5-year study period (hazard ratio = 0.57; P < 0.001). Patients who received BKP had higher 60-month adjusted survival rate (66.7%) than those who received PVP (58.7%) (P = 0.68). Cumulative 4-year mean overall costs after first diagnosis were lower for the BKP cohort (PVP: €42,510 vs. BKP: €39,014). Initial upfront higher costs driven by surgical treatment for patients who received BKP are offset by considerable pharmacy costs in patients who received PVP. There were differences between the values of painkiller consumption (PVP: €3321 vs. BKP: €2224). - Conclusion. - Results suggest a higher overall survival rate for operated than nonoperated patients with OVCF and indicate a potential survival benefit for patients who received BKP compared with patients who received PVP. The reasons merit further investigation. Total costs were lower after 4 years for patients who received BKP versus PVP due to less consumption of pharmaceuticals. - Level of Evidence: 3
Gesehen am 24.09.2020